Postpartum Diagnosed Wilsons Disease - Serpil Aydogmus; Serenat Eris; Secil Kurtulmus; Huseyin Aydogmus; Emre Ekmekci; Fatih Demir; Sefa Kelekci (Medicine Science, 2016)
Wilsons disease is an autosomal recessive genetic disorder in which defective biliary excretion of copper leads to its accumulation, especially in liver, brain and cornea. Clinical manifestations can vary widely. Untreated Wilsons disease may lead to subfertility and pregnancy complications such as; recurrent miscarriages, induced hypertension, preeclampsia, placental abruption and intrauterine growth restriction. Here we present a case with Wilsons disease (WD) diagnosed postpartum, underwent urgent cesarean section with a presumptive diagnosis of HELLP (Hemolysis, Elevated Liver Enzymes, Low Platelet Count) syndrome. Acute intravascular hemolytic anemia and thrombocytopenia in WD can be interpreted as a feature of HELLP syndrome besides acute liver failure. It should be considered in the diferrantial diagnosis. [Med-Science 2016; 5(1.000): 290-5]